Delirious - Art at the limits of reason 1950-1980 - Baum, Kelly 19XX-; Bradnock, Lucy; Ryan, Tina Rivers (The Metropolitan Museum of Art, 2017)
Addressing the maniacal, eccentric, and disorienting in artworks made between 1950 and 1980, Delirious situates a fascination with the absurd and irrational within the context of the violence and brutality witnessed during World War II as well as the rapid expansion of industrial capitalism in the 1950s. Skepticism of science and technology ... along with fear of its capability to promote mass destruction ... developed into a distrust of rationalism, which in the arts had the paradoxical result of extracting irrational effects from rational means. - This catalogue is published in conjunction with "Delirious: Art at the Limits of Reason, 1950-1980," on view at The Metropolitan Museum of Art, New York, from September 13, 2017 through January 21, 2018.
Includes bibliographical references and index
Keywords: Geschichte 1900-2000; Geschichte 1950-1980; Delirium in art -- Exhibitions; Art, Modern -- 20th century -- Themes, motives -- Exhibitions; Kunst; Irrationalität; Ausstellungskatalog; Ausstellungskatalog -- Metropolitan Museum of Art -- 13.09.2017-21.01.2018 -- New York, NY